When Reality Bites: Local Deaths and Vaccine Take-Up - Corrado Giulietti; Michael Vlassopoulos; Yves Zenou (Global Labor Organization (GLO), 2021)
In this study, we investigate whether COVID-19 deaths that occurred before vaccination rollouts impact subsequent vaccination take-up. We use data on local vaccination rates and COVID-19-related deaths from England measured at high geographic granularity. We find that vaccination take-up as of November 2021 is positively associated with pre-vaccine COVID-19-related deaths, controlling for demographic, economic, and health-related characteristics of the localities, while including geographic fixed effects. In addition, the share of ethnic minorities in a locality is negatively associated with vaccination rates, and localities with a larger share of ethnic minorities increase their vaccination rates if they are exposed to more COVID-related-deaths. Further evidence on vaccination intention at the individual level from a representative sample corroborates these patterns. Overall, our evidence suggests that social proximity to victims of the disease triggers a desire to take protective measures against it.
Keywords: H51; I12; 330; Vaccination hesitancy; COVID-19; Social interactions; Information; Behavior change